A high-absorption and self-driven salt-resistant black gold nanoparticle-deposited sponge for highly efficient, salt-free, and long-term durable solar desalination. Issue 6 (4th December 2018) - Liu, Yizhen; Liu, Zhipeng; Huang, Qichen; Liang, Xuechen; Zhou, Xuechang; Fu, Huide; Wu, Qixing; Zhang, Junmin; Xie, Wei
Abstract : The self-driven salt resistance mechanism and high solar absorption of BDS realized efficient and long-term durable solar desalination. Abstract : Although it is a promising approach for drinkable water production, solar desalination suffers from salt deposition, which reduces light absorption. This study presents a self-driven salt-resistant material, black gold nanoparticles-deposited sponge (BDS), for high-efficiency, salt-free and durable solar desalination. It utilizes the strong water absorption of melamine resin sponges, in which concentrated and dilute solutions exchange freely, driven by gravity and capillary forces. As such, the concentration of salt solution in the sponge cannot reach saturation to generate salt during solar evaporation. BDS can maintain an efficiency of 90% for 11 hours under 10 sun (10 kW m −2 ) and demonstrates a fresh water production rate of 12.74 kg m −2 h −1 with no visible salt deposition. Under natural sunlight, BDS maintains an efficiency of 80% for at least 4 days.